Isu-isu falsafah barat menurut pandangan islam - Nurfaraheen, Binti Mohd Nasir. (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study aimed to compare the issues in the philosophy, especially which related to the philosophy of mind. It will also examine the comparative philosophy ofan issue from the viewpoint of Islam and the West. Comparison between the viel1!point of Islam and the West would result in similarities and differences on that issue. The theory is set out in this issue are about the dualism, materialism, and Darwin. The description ofthe theory shows some acceptable and some more are in conflict with Islam. This research is centered on the study ofIslam as a benchmark. Fill-relevant content, and in accordance with accepted Islam in this study even though they are from Western philosophy. The theory of dualism is compatible with Islam and the west while the materialism theory opposedfrom Islam because the material aspects is more importantfor materialist without any soul or spiritual value.